2019
DOI: 10.1038/s41598-019-46239-z
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of biosignatures in a low-biomass simulation of martian sediments

Abstract: Discovery of a remnant habitable environment by the Mars Science Laboratory in the sedimentary record of Gale Crater has reinvigorated the search for evidence of martian life. In this study, we used a simulated martian mudstone material, based on data from Gale Crater, that was inoculated and cultured over several months and then dried and pressed. The simulated mudstone was analysed with a range of techniques to investigate the detectability of biosignatures. Cell counting and DNA extraction showed a diverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 49 publications
2
28
0
Order By: Relevance
“…It possible to retrieve infrared spectra in absorption or emission of samples in gas, liquid or solid state, with high spectral resolutions and in a wide spectral range. Although there are several studies using conventional infrared techniques for the study of biosignatures (Guido et al, 2012; Preston et al, 2014; Gordon and Septhon, 2016; Gaboyer et al, 2017; Igisu et al, 2018; Stevens et al, 2019), there is still a lack of reference in the use of synchrotron-based FTIR (SR-FTIR) techniques for this purpose. The synchrotron-based approach has the advantage of the high flux and broad range of energy, which allows the acquisition of fast spectra with high signal-noise ratio.…”
Section: Differentiating Biotic and Abiotic Elements Speciesmentioning
confidence: 99%
“…It possible to retrieve infrared spectra in absorption or emission of samples in gas, liquid or solid state, with high spectral resolutions and in a wide spectral range. Although there are several studies using conventional infrared techniques for the study of biosignatures (Guido et al, 2012; Preston et al, 2014; Gordon and Septhon, 2016; Gaboyer et al, 2017; Igisu et al, 2018; Stevens et al, 2019), there is still a lack of reference in the use of synchrotron-based FTIR (SR-FTIR) techniques for this purpose. The synchrotron-based approach has the advantage of the high flux and broad range of energy, which allows the acquisition of fast spectra with high signal-noise ratio.…”
Section: Differentiating Biotic and Abiotic Elements Speciesmentioning
confidence: 99%
“…Recent measurement campaigns demonstrate that LIMS systems not only have the measurement capabilities to analyze the elemental composition of minerals 11 , lunar regolith 12 , and meteorites 13 but can also identify putative fossil structures of micrometer dimensions embedded in a host material by monitoring elements relevant to life, such as carbon 14,15 . Measurements conducted on Martian mudstone analog material allowed the identification of the elemental signatures of single microbes that were inoculated artificially at low number density 16 . Moreover, LIMS systems, such as LAb-CosmOrbitrap 4 , have been able to successfully characterize the chemical composition of organics and tholins mixed with minerals 17,18 , making use of metal-organic clusters for identification and the high mass resolving power of Orbitrap to disentangle isobaric interferences of possible biogenic and non-biogenic molecular fragments.…”
Section: The Mars Scenariomentioning
confidence: 99%
“…LIMS modification of this instrument has been reported to measure ppbw level trace elements and routinely measure fine chemistry from a variety of samples ( Riedo et al, 2013a ; Neuland et al, 2016 ; Wiesendanger et al, 2017 ). Moreover, a number of reports have indicated that LIMS, particularly fs-LIMS, might be applicable to the detection of faint signatures of life from microscopic inclusions ( Tulej et al, 2015 ; Wiesendanger et al, 2018 ) and low-biomass Martian analogs ( Stevens et al, 2019 ; Riedo et al, 2020 ). However, the field of study of early and primitive life remains profoundly complex ( Brasier and Wacey 2012 ; Westall et al, 2015 ; Wacey et al, 2016 ) with no single chemical criterion that can be assigned as definitive proof of biogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in performance occurs due to the strict constraints on size, power consumption, and weight of the scientific payload. Therefore, the development of new miniature instruments and analytical methods with improved capabilities is a continuously pressing issue (Li et al, 2017;Arevalo et al, 2018;Stevens et al, 2019;Wurz et al, 2020).…”
Section: Introductionmentioning
confidence: 99%